Effects of Prognostic Nutrition Index, Neutrophil/Lymphocyte Ratio, and C-reactive Protein/Albumin Ratio on Prognosis Undergoing Open Heart Surgery - Anil Kilinc; Nilay Tas; Melih Urkmez; Ebru Canakci; Ilker Coskun; Merve Elif Demirhan (Haseki Tıp Bülteni)
Aim: Deficiencies in preoperative nutritional status increase the incidence of negative postoperative events. In this study, we aimed to investigate the effect of the prognostic nutrition index (PNI), neutrophil-to-lymphocyte (N/L) ratio, and C-reactive protein (CRP)-to-albumin (CRP/Alb) ratio on postoperative prognosis in patients undergoing open-heart surgery. Methods: Patients undergoing primary open-heart surgery in our hospital from December 2021 to August 2023 were screened for PNI, N/L ratio, and CRP/Alb ratios, along with durations in intensive care, total hospitalization, and 30-day mortality rates. Binary logistic regression and robust regression analyses were used for the statistical analysis of this cross-sectional study. Results: The study included a total of 437 cases. All patients had a mean PNI of 49.35±7.70. A one-unit increase in PNI value reduced intensive care duration by 0.495 units (p=0.049), while it reduced discharge duration by 0.101 units (p<0.001). A one-unit reduction in PNI value increased mortality by 1.07 times (p=0.002). The other variables showed no significant effects on intensive care duration, total hospitalization, and 30-day mortality rates. Conclusion: PNI, a marker of inflammatory and immune processes, may be a beneficial variable for estimating postoperative prognosis among patients undergoing open heart surgery.